2016
DOI: 10.1186/s12891-016-1211-8
|View full text |Cite
|
Sign up to set email alerts
|

Distal radius reconstruction with vascularized proximal fibular autograft after en-bloc resection of recurrent giant cell tumor

Abstract: BackgroundGiant cell tumors (GCTs) located in the distal radius are likely to recur, and the treatment of such recurrent tumors is very difficult. Here, we report our clinical experience in distal radius reconstruction with vascularized proximal fibular autografts after en-bloc excision of the entire distal radius in 17 patients with recurrent GCT (RGCT) of the distal radius.MethodsAll 17 patients with RGCT in distal radius underwent plain radiography and/or magnetic resonance imaging (MRI) of the distal radiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
(23 reference statements)
0
17
0
2
Order By: Relevance
“…Proximal fibular autograft has disadvantages, including lack of blood supply and osteogenic cells, potential immunologic reactions, and possibility of collapse secondary to bone allograft absorption. Therefore, bone allografts are not the best choice for reconstruction and do not result in very satisfactory outcomes [13]. The use of megaprosthetic implant gained the worldwide recognition for tumor reconstruction, however, due to the large portion of implant and major resection of the tumor, the surgery needs free flap for soft tissue coverage [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proximal fibular autograft has disadvantages, including lack of blood supply and osteogenic cells, potential immunologic reactions, and possibility of collapse secondary to bone allograft absorption. Therefore, bone allografts are not the best choice for reconstruction and do not result in very satisfactory outcomes [13]. The use of megaprosthetic implant gained the worldwide recognition for tumor reconstruction, however, due to the large portion of implant and major resection of the tumor, the surgery needs free flap for soft tissue coverage [19].…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor (GCT) is a type of benign tumor which is locally aggressive and has the capability to metastasize [[1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14]]. It represents approximately 5% of all primary bone tumors [2,[2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells remaining or being implanted in the surgical site during surgery usually causes local recurrence of GCT [22]. Previous studies have shown that en-bloc resection of GCT is very effective in reducing recurrence [23]. However, when the GCT is located around the knee, en-bloc resection is not recommended if we want to save the knee joint.…”
Section: Extensive Curettage Can Reduce the Risk Of Recurrencementioning
confidence: 99%
“…Non-vascular autografts have many advantages since they contain normal bone structure and are free from disease transmissions. However, these grafts may also have some complications (such as nonunion, donor complications), which may eventually lead to unsatisfactory outcomes [23]. Since some cases of our patients presented with the non-vascular bular autografts collapse in wrist and knee reconstruction, we did not repair massive bone defects only by using non-vascular bular grafts.…”
Section: Extensive Curettage Can Reduce the Risk Of Recurrencementioning
confidence: 99%